EFEKTIVITAS PENDEKATAN STM TERHADAP HASIL BELAJAR BIOLOGI SISWA MA PALAPA NUSANTARA NW SELEBUNG KELAS X TAHUN AJARAN 2013/2014 - Indra Himayatul Asri (Cocos Bio, 2016)
this reserch was aimed at knowing whether science and peopleâ€™s technology (STM) was effective toward studentâ€™s biology learning achiement of the tenth grade of MA Palapa Nusantara NW Selebung in the academic year 2013-2014. This reserch was experimental reserch with post-test only control  group desaign. The population was all students of the tenth grade MA Palapa Nusantara NW Selebung and the sample was X-A was experimen group and X-B was control group. The research instrument was 20 items of multiple choice. The data were  were analyzed using homogeneity with variant test and normality test with chi-square. The hypothesis was tested through t-test where t-test was higher than t-table (5,02 1,98. Meanwhile, the result of analysis showed that the experimeth groupâ€™s mean score was 76,75 and the control group was 60,16 it meant that Ha was accepted and the implementation of  saince and peopleâ€™s technology was significantly effective toward students,biology learning achiievement of the tenth grade of MA Palapa Nusantara NW Selebung in academic year 2013-2014.